Răspuns :
Explicație pas cu pas:
a)
[tex] \frac{2}{2} + \frac{3}{2} = \frac{5}{2} [/tex]
b)
[tex] \frac{3}{4} - \frac{2}{4} = \frac{1}{4} [/tex]
c)
[tex] \frac{5}{3} + \frac{5}{2} = \frac{5 \times 2 + 5 \times 3}{6} = \frac{25}{6} [/tex]
d)
[tex]4 + \frac{15}{1} + \frac{25}{2 } = \frac{4 \times 2 + 2 \times 15 + 25}{2} = \frac{8 + 30 + 25}{2} = \frac{63}{2} [/tex]
cred ca asa este scris
e)
[tex] \frac{100}{0} + \frac{45}{0} = 0[/tex]
f)
[tex] \frac{13}{2} + \frac{1}{100} = \frac{13 \times 50 + 1}{100} = \frac{650}{100} = \frac{65}{10} [/tex]
g)
[tex] \frac{15}{2} - \frac{14}{2} = \frac{1}{2} [/tex]
h)
[tex] \frac{2}{2} + \frac{2}{3} + \frac{2}{4} = \frac{2 \times 6 + 2 \times 4 + 2 \times 3}{12} = \frac{12 + 8 + 6}{12} = \frac{26}{12} = 3[/tex]
i)
[tex] \frac{4 - 3}{3} + \frac{5 \times 3}{3} = \frac{1 + 15}{3} = \frac{16}{3} [/tex]
j)
[tex] \frac{6 - 5 - 4}{3} = \frac{ - 3}{3} = - 1[/tex]
k)
[tex] \frac{3 + 4 - 5}{2} = \frac{7 - 5}{2} = \frac{2}{2} = 1[/tex]
l)
[tex]0 + 2011 = 2011[/tex]